2020
DOI: 10.3390/beverages6020035
|View full text |Cite
|
Sign up to set email alerts
|

Happy Hour? A Preliminary Study of the Effect of Induced Joviality and Sadness on Beer Perception

Abstract: Our emotions influence our perception. In order to determine whether emotion influences the perception of beer, 32 participants watched either a scene from the movie Wall-E to induce joviality, or a short clip from the Shawshank Redemption to induce sadness. The participants were then required to sample up to 250 mL of Yenda Pale Ale beer and rate it on a variety of taste and flavor characteristics (e.g., bitterness), before completing the Positive and Negative Affect Schedule-X (PANAS-X). The data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…Here, reading positively-framed vignettes (e.g., making a good beer or contributing to the community) may have primed people (consciously or unconsciously) to feel good about themselves (hold positive feelings about how moral they are), and this information may have been used as a source of information in judgments of the beer (those people who feel positive will rate the beer more positively, i.e., as being more refreshing). Clearly this explanation is speculative, but it is consistent with evidence showing that a manipulated mood impacts beer taste perception [39].…”
Section: Perceptionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, reading positively-framed vignettes (e.g., making a good beer or contributing to the community) may have primed people (consciously or unconsciously) to feel good about themselves (hold positive feelings about how moral they are), and this information may have been used as a source of information in judgments of the beer (those people who feel positive will rate the beer more positively, i.e., as being more refreshing). Clearly this explanation is speculative, but it is consistent with evidence showing that a manipulated mood impacts beer taste perception [39].…”
Section: Perceptionsupporting
confidence: 77%
“…Second, pleasantness of taste and aftertaste, quality, and willingness-to-pay are all global valence judgements which have been used in previous research [6]. Past research [39] has established that participants are able to evaluate the global (e.g., pleasantness) and specific (e.g., sweetness) characteristics of beer uniquely.…”
Section: Beer Taste Perception Questionnairementioning
confidence: 99%
“…Previous research has also shown that when consumers are induced into negative emotions (e.g., via music or movie clips), they tend to perceive a beer’s flavor as more alcoholic, less sweet, and/or more bitter [ 38 , 39 ]. In Experiment 1, the auditory conditions that participants reported as the most negative were the low-frequency/low-pressure can-opening/can-pouring ones.…”
Section: Discussionmentioning
confidence: 99%
“…Positive emotions are multifaceted and can include states such as joviality, serenity, and engagement. Although positive emotions have traditionally been treated as a uniform state, it may be easier to induce and focus on specific facets of positive emotions which may be most strongly connected to alcohol use (Desira et al, 2020). Ultimately, we believe that rigorously testing positive reinforcement of alcohol use as value-based decision-making may be even more important than negative reinforcement due to the robust effect of positive affect on alcohol use in everyday life (Dora et al, 2022a).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%